Assessment of the conservation status of reinforced concrete viaducts: a case study of the Recife/Gravatá-PE railroad - Bento, Adegilson José; Monteiro, Eliana Cristina Barreto (National Journal of City Management, 2024)
The deterioration of engineering landmarks, such as bridges and viaducts, is a global issue. The solution lies in the maintenance and conservation of these structures, through a genuine understanding of their conditions and regular inspections. The objective of this study was to assess the overall state of conservation of viaducts, Special Art works (SAW’s) located in the designated section of the railway, Central Trunk Line of Pernambuco – LTCPE. To systematically conduct the study, the survey method prescribed by NBR 9452: Inspection of Bridges, Viaducts, and Concrete Walkways - Procedure (Brazilian Association of Technical Standards – ABNT, 2023) was adopted, dividing it into cadastral (preliminary) and detailed inspections, including “graphic and quantitative mapping of anomalies of all visible and/or accessible elements of the SAW" (ABNT, 2023. p. 5). The results revealed issues such as water accumulation, sedimentation, stains, and efflorescence, along with water infiltration in the concrete, attributed to deficient or absent drainage due to incorrect system design and lack of maintenance. Concrete deterioration, and reinforcement corrosion were also, with corrosion stains, fissures, and exposure of reinforcements, caused by carbonation resulting from design errors (insufficient covering) and/or execution errors (formwork, concrete pouring, and form removal). These issues can be initially addressed through corrective maintenance, repair of affected areas, improvement of the drainage system, filling or sealing of fissures, installation of efficient drainage systems, and other repair works. A stability study of these structures is crucial to ensure lasting solutions.
Keywords: Inspection; Special work of art; SWA; Viaducts